Optical Soliton Perturbation with Dispersive Concatenation Model Having Power- Law of Self-Phase Modulation: Semi-Inverse Variation - Kohl, Russell W.; Biswas, Anjan; Yildirim, Yakup; Alshomrani, Ali Saleh (Journal of Applied Nonlinear Dynamics, 2026)
The current paper recovers a bright 1–soliton solution to the dispersive concatenation model that is considered with power–law of nonlinear self–phase modulation. The semi–inverse variational principle is applied to recover the soliton solution. The parameter constraints that naturally emerge from the analysis for the existence of bright solitons are also presented in the work.